The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10096-020-04129-7
|View full text |Cite
|
Sign up to set email alerts
|

Lyme neuroborreliosis in Swedish children—PCR as a complementary diagnostic method for detection of Borrelia burgdorferi sensu lato in cerebrospinal fluid

Abstract: The aim of this study was to evaluate polymerase chain reaction (PCR) as a diagnostic method for the detection of Borrelia burgdorferi s.l. in CSF of Swedish children with LNB. This study was performed retrospectively on CSF and serum samples collected from children evaluated for LNB (n = 233) and controls with other specific neurological disorders (n = 59) in a Swedish Lyme endemic area. For anti-Borrelia antibody index, the IDEIA Lyme Neuroborreliosis kit (Oxoid) was used. Two in-house real-time PCR assays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…We included fifty-nine patients examined for LNB, with samples stored at − 20 °C containing at least 0.5 mL CSF sample material. We detected Borrelia DNA in one clinical sample from a patient diagnosed with LNB resulting in a clinical sensitivity of 11% (1/9), which is within range of previous reports 9,10,[23][24][25] . Positive PCR results for detection of Borrelia targets in CSF samples often have high cycle threshold values (> 38), indicating low amounts of targets in the samples 10,26 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We included fifty-nine patients examined for LNB, with samples stored at − 20 °C containing at least 0.5 mL CSF sample material. We detected Borrelia DNA in one clinical sample from a patient diagnosed with LNB resulting in a clinical sensitivity of 11% (1/9), which is within range of previous reports 9,10,[23][24][25] . Positive PCR results for detection of Borrelia targets in CSF samples often have high cycle threshold values (> 38), indicating low amounts of targets in the samples 10,26 .…”
Section: Discussionsupporting
confidence: 84%
“…In general, the analytical sensitivity and specificity of PCR assays detecting Borrelia in CSF samples are high 9 , 26 , 27 , but the clinical sensitivity on CSF samples is suboptimal (median sensitivity of 40%) 25 . Consequently, it has been suggested that larger CSF sample volumes (> 1 mL) in combination with centrifugation may improve the possibility of detecting the Borrelia target by PCR 8 , 10 , 20 , 23 . A different approach enabling enrichment of Borrelia DNA prior to PCR could be to culture the clinical CSF samples.…”
Section: Discussionmentioning
confidence: 99%
“…With the performance of ELISA and Western blot both lackluster in detecting Lyme disease, it is about time patients and physicians have improved technology. [68]. The tests were retrospective, allowing the researchers to categorize the children into groups of "Definite," "Possible," and "non-Lyme" in terms of their Lyme disease status; another group of children not exposed to Lyme disease was used as a control group.…”
Section: Elisamentioning
confidence: 99%
“…The tests were retrospective, allowing the researchers to categorize the children into groups of "Definite," "Possible," and "non-Lyme" in terms of their Lyme disease status; another group of children not exposed to Lyme disease was used as a control group. The PCR tests identified only a small portion of the definite Lyme cases as positive for Lyme disease (5%) while changing one child from the "Possible" group to "Definite" and another child from the "non-Lyme" group to "Definite" [68]. The conclusion that Skogman and her colleagues drew from the results was that these two PCR tests were better suited to a complementary role in Lyme disease testing due to its very low sensitivity but could still remain useful for its ability to catch certain cases that would otherwise not be classified as a Lyme infection.…”
Section: Elisamentioning
confidence: 99%
“…Currently, Ixodes tick-borne borreliosis is widespread in the United States, Canada, Russia, and some Western European countries [3,4]. For example, cases are reported from the North West District to the Far East territories in Russia, including Sakhalin [5].…”
Section: Introductionmentioning
confidence: 99%